IMPLEMENTATION OF STRATEGIC LEADERSHIP IN THE AT-TAQWA PAMULANG ISLAMIC EDUCATIONAL INSTITUTION, SOUTH TANGERANG CITY, BANTEN: IMPLEMENTATION OF STRATEGIC LEADERSHIP IN THE AT-TAQWA PAMULANG ISLAMIC EDUCATIONAL INSTITUTION, SOUTH TANGERANG CITY, BANTEN - Sastri, Enan Trivansyah; Husainah, Nazifah; Wicaksono, Digantara (PENANOMICS: International Journal of Economics, 2025)
This research aims to analyze the strategic leadership used by the Islamic Education Institute At-Taqwa Pamulang Foundation, South Tangerang City. The application of strategic leadership is one of the efforts to improve the quality carried out by At-Taqwa Pamulang Islamic Elementary and Middle School, South Tangerang City. This research uses qualitative methods with the research location at At-Taqwa Pamulang Islamic Elementary and Middle School, South Tangerang City. Data was obtained through observation, interviews and documentation. Interviews were conducted with school principals, teachers, employees and parents. Respondents for the interview were 30 people. This research concludes that Strategic leadership has been implemented at At-Taqwa Islamic Elementary and Middle School. The application of strategic leadership takes the form of schools preparing plans to achieve the expected educational goals. School planning is based on the school's vision, mission and goals, and takes into account the school's SWOT analysis. Schools prepare RKS, RAPBS, and SOP. The implementation of strategic leadership results in improved school quality. This research contributes to the literature in examining the application of strategic leadership in Islamic educational institutions in Indonesia.